A New Dressing System Reduces the Number of Dressing Changes in the Primary Total Knee Arthroplasty: A Randomized Controlled Trial - Su, Shilong; He, Juan; Wang, Chenggong; Gao, Fawei; Zhong, Da; Lei, Pengfei (Frontiers in Surgery, 2022)
Purpose We devised a novel dressing system to accelerate the recovery after total knee arthroplasty (TKA). The purpose of this study was to assess the clinical outcomes and economic expenses of the new dressing system. Methods In this randomized and controlled trial, we enrolled 98 patients who underwent the first unilateral TKA between September 2020 and June 2021. The patients were randomly assigned to one of two groups: the intervention (the new dressing system group) or the control (the traditional gauze dressing) group. We gathered and evaluated patient data including age, gender, body mass index, surgical side, number of dressing changes, post-operative hospital stay, dressing-related expense, satisfaction, pain and function scores, wound scores and wound-related complications. Results The number of dressing changes and post-operative hospital stay in the intervention group were significantly less than in the control group (p = 0.000, p = 0.002). Satisfaction in the intervention group was significantly higher than in the control group’s (p = 0.000). There were no significant differences between the two groups in dressing-related expense, pain and function scores. During the one month follow-up, the intervention group’s Stony Brook Scar Evaluation Scale (SBSES) was considerably higher than the control group’s (p = 0.012). Conclusion The new dressing system can reduce the number of dressing changes and post-operative hospital stays while increasing patient satisfaction with no difference in medical costs in TKA. This wound dressing system has potential for application in TKA Chinese Clinical Trial Registry: ChiCTR2000033814; Registered 13 June 2020.